Pengembangan Aplikasi Perangkat Bergerak Penghubung Pengelola Perkemahan dengan Wisatawan berbasis Android (Studi Kasus :Perkemahan Bedengan) - Aditya Negara; Agi Putra Kharisma; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Perkemahan Bedengan is a campsite located in the city of Malang. From the interviews that have been carried out it was concluded that Perkemahan Bedengan had problems in promoting the campsite and arranging reservations. Tourists who want to camp also have problems in the form of the difficulty of booking camps and lack of information about campsites. From the results of the interview, it can be concluded that a system of connecting camp managers and tourists is needed. The system was built based on Android Operating System because the Android operating system has controlled more than 90 percent of the smartphone market in Indonesia.Based on the results of the needs analysis, two systems are needed for this research. The first system is a system for campsite managers who can manage campsites and accept or reject orders. The second system is a system for tourists. This system can reserve campsites and provide camp reviews.Based on the results of testing the validity of 22 cases in this system it was found that 22 cases passed the test and were valid. And the usability test results using the USE questionnaire method obtained results in all aspects above 71% and declared Eligible.